Does Ignorance of Economic Returns and Costs Explain the Educational Aspiration Gap? Evidence From Representative Survey Experiments - Philipp Lergetporer; Katharina Werner; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
The gap in university enrollment by parental education is large and persistent in many countries. In our representative survey, 74 percent of German university graduates, but only 36 percent of those without a university degree favor a university education for their children. The latter are more likely to underestimate returns and overestimate costs of university. Experimental provision of return and cost information significantly increases educational aspirations. However, it does not close the aspiration gap as university graduates respond even more strongly to the information treatment. Persistent effects in a follow-up survey indicate that participants indeed process and remember the information. Differences in economic preference parameters also cannot account for the educational aspiration gap. Our results cast doubt that ignorance of economic returns and costs explains educational inequality in Germany.
Keywords: D83; I24; J24; H75; 330; inequality; higher education; university; aspiration; information; returns to education; survey experiment